THE BREEDING OF INDEPENDENCE BY CHILDREN OF PRIMARY AGE - Dudnyk, Nadiia (Mountain School of Ukrainian Carpaty, 2018)
The purpose of the article is to isolate the problem of formation of independence as an educational task in the process of upbringing of a harmoniously developed personality, which is formed at the preschool age and is decisive in the process of formation of a harmonious personality, capable of evaluating one’s own abilities, striving for self-development and self-realization. The article deals with the problem of formation of independence of preschool children as an educational task. During the writing of the article, a paradigm method was used to reveal the educational potential of the educational foundations of the development of independence as a personality trait from the standpoint of pedagogical science; Synergetic method for argumentation of pedagogical ideas of teachers by means of nonlinear connections between theories and concepts of modern education. The author analyzes the problem of research in psychological and pedagogical science, outlines issues that are posed in the development of a child of preschool age. The author stresses the need to develop a strategy for modern education, which should create a special development environment, methodological conditions for the formation of independence by children of preschool age in the process of a child’s development. As a psychological precondition, the emotional component that contributes to the manifestations of the socially useful affairs of a preschool child enables it to master self-directed activities, develop communicative skills in co-operation with coevals. The role of teachers in the creation of a specially organized developmental environment and the initiative of children in the game, free activities, in didactic classes are defined as a prerequisite for the formation of the independence of preschoolers. The purpose of the article is to isolate the problem of formation of independence as an educational task in the process of upbringing of a harmoniously developed personality, which is formed at the preschool age and is decisive in the process of formation of a harmonious personality, capable of evaluating one’s own abilities, striving for self-development and self-realization.